Meat substitutes in Media Discourse - Wenxuan Guo (International Journal of Food Studies)
Shifting from meat consumption is critical for future dietary evolution. Mainstream newspapers and social media are the leading platforms for expressing this opinion. By analysing the media discourse, the proponents of the shift from meat, to plant-based meat and cultured meat were identified. The objectives were: a) to identify themes, word frequencies, and sentiment related to meat substitutes, b) to determine Chinese perceptions of the two meat substitutes, and c) to determine which food functions are of concern to Chinese consumers. Between July 2016 and July 2022, the researcher gathered data from People’s Daily and China Daily online outlets and user comments. 574 news articles and 2,345 online comments were extracted. Three techniques were applied: sentiment analysis, thematic analysis, and word cloud analysis. The results revealed that newspapers reported positively on meat substitutes, yet user comments showed negative public perception. Chinese people held positive attitudes toward plant-based meat and negative attitudes toward cultured meat. Thus, the insights from the media discourse provided valuable indicators for stakeholders to develop sustainable food education and consumption strategies.